Turbulence‐Based Model for Subthreshold Aeolian Saltation. Issue 15 (31st July 2020) - Rana, Santosh; Anderson, William; Day, Mackenzie
Abstract: Sand transport initiation and cessation occurs when the surface shear velocity exceeds a fluid threshold and falls below an impact threshold, respectively. Even when average shear velocity is below fluid threshold, turbulent fluctuations can initiate saltation, leading to turbulence‐driven transport intermittency. We leveraged the dynamic properties of large‐eddy simulation to recover a shear velocity time series due to atmospheric turbulence and recover a probability density function for saltation based on the frequency of events where wind has previously exceeded fluid threshold but not yet dropped below impact threshold. By conditionally sampling, we can quantitatively predict the frequency of intermediate saltation. Results show that a compensated, subthreshold shear velocity exhibits linear dependence upon the actual shear velocity. This compensated shear velocity compares favorably against field data. Model performance under terrestrial and Mars conditions is also shown. Plain Language Summary: Windblown sand transport occurs due to aerodynamic drag imposed by the aloft atmosphere. Models for sand mass flux make use of a nonlinear dependence upon the so‐called shear velocity, which is derived from aerodynamic drag: Sand transport begins and ends when the shear velocity exceeds a fluid threshold and falls below an impact threshold, respectively. Using sand transport and wind data from two high‐frequency field campaigns, and from a relatively lower‐frequency field campaign encompassing nine months of continuous measurements, systematic correlation is recovered in the nature of "subthreshold" transport. Using computational fluid dynamics simulation of wind turbulence, stress statistics are studied and an accompanying prognostic model is recovered. The model performs well against the field data. The implications for this on Earth and Mars are shown. Key Points: Aeolian sand transport responds to turbulent fluctuations in the atmosphere that can be accounted for probabilistically Conditionally sampled shear velocity scales linearly with actual time‐averaged shear velocity for subthreshold transport The proposed aeolian transport model can be readily generalized to Mars, where subthreshold transport is significant